Diversitas Gastropoda pada Akar Mangrove di Pulau Sirandah, Padang, Sumatera Barat - Hirzan Riyandi; Indra Junaidi Zakaria; Izmiarti Izmiarti (Universitas Andalas, 2017)
Currently, there are a lot of activities in Sirandah Island, such as tourism activities and deforestation to support the activities. Mangrove forest distruction makes a useable area might have negative effect to mangrove ecosystem itself or mollusc community. This research was conducted on mangrove roots area from February until October 2016. The aim of this research is to know the diversity of Gastropods on the roots of the mangrove. This research was conducted using survey method and purposive sampling method to collecting data. We recorded 8 genera of Gastropods belong to 8 families, named Cerithium, Conus, Ellobium, Littorina, Melongena, Nerita, Cymatium and Turbo. The highest abundance was found in the genus of Littorina with 59.33 individuals/tree. Based on location, abundance ranged from 4.33-60.33 individuals/tree with the highest abundance on mangrove roots of Barringtonia asiatica. Diversity indices of Gastropods on mangrove roots in Sirandah Island ranged from 0.77 to 1.42 which is relative low range.